Excite phonetics and phonology learning through fun online transcription activity - Idrus, Faizah; Yusof, Siti Umairah; Mohd Kamalludeen, Rosemaliza (Centre for Global Open Access Learning - Immersive Technology & Quality Assurance (GOAL-ITQAN), Universiti Sains Islam Malaysia (USIM), 2017)
Highlights: To enhance language learning, research has shown that language instruction with computer technology was more effective than instruction without it (Grgurovic, Chapelle & Shelly, 2011). Grgurovic et al. further elaborated that Computer-aided Language Learning (CALL) specialists “aim to create ideal language learning conditions through strategic use of pedagogies developed around interactive video, learner-computer interactions, corrective feedback, tasks with linguistic support, and intercultural communication” (p.166). Therefore, in order to make learning challenging subject matter such as Phonetics and Phonology exciting and effective, usage of technology tools are appealing to most language educators in today’s context. Learning about Phonetics and Phonology is no easy feat. Students will usually find this area of the Teaching English as a Second Language (TESL) program one of the most challenging. This study has leveraged on usage of technology, specifically using video and YouTube to assist student teachers in mastering the knowledge and skills spelled out in Phonetics and Phonology course in the Teaching English as a Second Language Program (TESL) at IIUM. It was found that students find their task engaging, exciting, and impactful in their learning of Phonetics and Phonology.